Hubungan Perilaku Dengan Kejadian HIV/ AIDS Di Ranah Minang - Sri Handayani (Jurnal Sehat Mandiri, 2019)
The Minang realm still has the top position in the AIDS incidence rate with a case rate of 18.8. This condition is above the national AIDS case rate (17.2). Minang is a tribe whose philosophy is Adat Basandi Syarak, Syarak Basandi Kitabullah is based on Islamic law in the Minangkabau culture. In addition, in his administration in the Minahasa District there are Regulations No. 6 of 2003 and Regulations of the Province of West Sumatra no 9 of 2000. Supposedly with this philosophy and policy can prevent the development of HIV / AIDS incidence. The purpose of this study was to examine in depth about the behavioral conditions associated with the incidence of HIV / AIDS. This research uses descriptive approach, case control design. Data were collected through questionnaire distribution using a quota sampling technique of 28 cases and 28 controls. The results of the study of the behavior obtained risky sexual behavior in 57 cases, 1% and 25% control. Drug use behavior is risky in cases of 10, 7% and controls 3, 6%. Behavior using tattoos is at risk in cases of 14.3% and controls 3.6%. There is a significant relationship between sexual behavior (P 0.014) with the incidence of HIV / AIDS. It is recommended that the government and traditional stakeholders be actively involved in managing the risk of HIV / AIDS.